2015
DOI: 10.3390/cancers7030843
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs: The Key Players in Glioma Pathogenesis

Abstract: Long non-coding RNAs (LncRNAs) represent a novel class of RNAs with no functional protein-coding ability, yet it has become increasingly clear that interactions between lncRNAs with other molecules are responsible for important gene regulatory functions in various contexts. Given their relatively high expressions in the brain, lncRNAs are now thought to play important roles in normal brain development as well as diverse disease processes including gliomagenesis. Intriguingly, certain lncRNAs are closely associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 129 publications
(165 reference statements)
0
92
0
Order By: Relevance
“…Brain glioma is the most common primary tumor of the central nervous system, and one of the main causes of death in patients with intracranial tumors . The poor prognosis and high recurrence rate of glioma is largely due to the abundant blood flow, rapid growth, susceptibility of invasion to surrounding normal brain tissues and resistance to radiotherapy and chemotherapy . The tumorigenesis of glioma is biologically complex, involving a series of pathophysiological changes, and expression changes of many genes and signaling pathways .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain glioma is the most common primary tumor of the central nervous system, and one of the main causes of death in patients with intracranial tumors . The poor prognosis and high recurrence rate of glioma is largely due to the abundant blood flow, rapid growth, susceptibility of invasion to surrounding normal brain tissues and resistance to radiotherapy and chemotherapy . The tumorigenesis of glioma is biologically complex, involving a series of pathophysiological changes, and expression changes of many genes and signaling pathways .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of microarray and high‐throughput sequencing technologies in recent years, accumulating studies have shown that a large number of differentially expressed lncRNAs between normal brain tissues and different grades of gliomas were verified, and many lncRNAs extensively participate in the tumorigenesis of glioma by modulating the proliferation, apoptosis, invasion and metastasis of glioma cells. lncRNAs can not only be important markers for the diagnosis of glioma, but used as important prognostic indicators in patients with glioma . However, despite the efforts made on the study of the tumorigenesis and progression of glioma, the clinical outcome remains unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has shown that lncRNAs are responsible for essential gene regulatory functions in various tissues (Guttman et al, ; Liu et al, ; Zhu et al, ). As in brain, research has shown that many lncRNAs are highly expressed in the brain (Kiang, Zhang, & Leung, ), and taken specific expression means specific function into consideration, high expression means important functions in normal brain development and brain‐related diseases, such as glioma (Y. Wang & Lan, ; O. Wang et al, ; Yu et al, ). Actually, several lncRNAs have been proven to haa ve function in brain development (Sauvageau et al, ; Trojan et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows functionally validated lncRNAs involved in embryogenesis that have also been identified as oncogenic or tumour suppressors in glioma cancer biology 31, 46, 47, 48, 49…”
Section: Functions Of Lncrnas In Glioma Biologymentioning
confidence: 99%